Meningkatkan Kapasitas Sistem Administrasi Pemerintah Untuk Kepentingan Bangsa Dan Persaingan Global - Gedeona, Hendrikus (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
Global competitive and change era not only demand government bereaucracy being more self-introspection, but also capable to enhance government administration system capacity which has quality and ability to complete. Government administration system enhancing strategy must be done in individual, group, organization and management contexts as a sustainability system to in crease competency and ability to solve problem. Implementation of this strategy will be success if supported by outer shifs and inner shifs in the contects of four components said early before.